A proposed descriptive metadata schema for the admission and discharge form of the patient health record - Opina, Lean John A. (2006)
Data collection has been a relevant facet of research and development. The generation of electronic resources became available in cheaper and more convenient means as the manner of collecting and processing data evolved with technology. However, the demand for accurate and comprehensive data recovery and retrieval intensified due to the inconceivable growth of electronic resources. The situation is evident in many institutions. For hospitals, in particular, this is manifested in the efforts to incorporate electronic media in order to minimize expenses in the generation, maintenance and storage of numerous paper-based records. With this in mind, it is relevant to observe current data collection trends and record keeping practices to come up with means that would facilitate resource discovery.